Pakcoy (Brassica chinensis L.) Growth Using Moringa Leaf Extract with the Addition of Red Onion Skin - Widjaya, Dwi Putri; Suparti, S (Universitas Muhammadiyah Surakarta, 2023)
Pakcoy is a vegetable that contains carbohydrates, fat, Fe, P, Ca, vitamins A, B, C, E, and K. moringa leaves and shallot skin are one of the organic wastes that can be used as additional media for plants. The purpose of the research is to identify the effect of moringa leaf extract and shallot skin on the growth of pakcoy plants. This research used a CRD (completely randomized design) with 1 factor 4 repetitions. The factors used were extract of moringa leaved and shallot skin which included P0=0% concentration, P1=20% extract concentration, P2=40% extract concentration, P3=60% extrac concentration. Parameters observed wre plant height and number of leaves. Data were examined with the non-parametric Statistical test, namely the Kruskal Wallis and continued with Duncan’s Multiple Range Test to determine the best growth and yield in that treadment. The results of data analysis showed that the best treatment. The results of data analysis showed that the best treatment for pakcoy growth was in treatment P1 with an average plant height of 7.725 cm and average number of leaves of 2.5 leaves. The lowest treatment of pakcoy growth was in treatment P3 with an average plant height of 4.875cm and average number of leaves of 0.25.